Mannequette: Understanding and enabling collaboration and creativity on avant-garde fashion-tech runways - SEYED, Teddy (Institutional Knowledge at Singapore Management University, 2019)
Drawing upon multiple disciplines, avant-garde fashion-tech teams push the boundaries between fashion and technology. Many are well trained in envisioning aesthetic qualities of garments, but few have formal training on designing and fabricating technologies themselves. We introduce Mannequette, a prototyping tool for fashion-tech garments that enables teams to experiment with interactive technologies at early stages of their design processes. Mannequette provides an abstraction of light-based outputs and sensor-based inputs for garments through a DJ mixer-like interface that allows for dynamic changes and recording/playback of visual effects. The base of Mannequette can also be incorporated into the final garment, where it is then connected to the final components. We conducted an 8-week deployment study with eight design teams who created new garments for a runway show. Our results revealed Mannequette allowed teams to repeatedly consider new design and technical options early in their creative processes, and to communicate more effectively across disciplinary backgrounds.